Preparation And Characterization Of Adsorbents From Oil Palm Fronds Coated With Nanochitosan From Green Mussel Shells - Manullang, Poyder; Herlinawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the characteristics of adsorbents made from activated carbon of oil palm fronds coated with nanochitosan from green mussel shells. The provision of adsorbents is carried out by the method of coating. The FTIR characterization results show the presence of N-H groups owned by chitosan, namely at wavenumbers between 3500-3297.33 cm-1. BET characterization gives a carbon surface area yield of 45,657 m2/g, the surface area of activated carbon is 14,255 m2/g and the surface area of activated carbon is coated with nanochitosan 57,057 m2/g. The pore volume of carbon also changed, namely carbon by 0.055 cm3 / g, activated carbon by 0.040 cm3 / g and activated carbon coated with nanochitosan by 0.070 cm3 / g. The results showed that the pore properties of activated carbon changed after coating with nanochitosan which was related to the absorption of activated carbon